2017
DOI: 10.1080/02699052.2017.1346285
|View full text |Cite
|
Sign up to set email alerts
|

The fate of asymptomatic severe carotid stenosis in the era of best medical therapy

Abstract: The most recent series of ACAS ≥70% and BMT had an overall stroke rate which is relatively low; however, the risk of developing symptoms is still relevant (3.4%/year).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Whereas the historical ACAS/ACST trials reported a 2% to 3% risk of stroke per year on medical therapy, a 2017 metaanalysis of more than 70% asymptomatic carotid stenosis reported that modern best medical therapy carries a pooled risk of 1.6% per year for ipsilateral stroke and 3.4% per year for transient ischemic attack. 20 However, the high variability of the stroke rate per year in these studies (0.34% as suggested by Marquardt et al 21 to 5.4% by the Aggressive Medical Treatment Evaluation for Asymptomatic Carotid Artery Stenosis study 22 ) made the results difficult to interpret. There are currently no data on the natural history of asymptomatic carotid stenosis in octogenarians.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 87%
“…Whereas the historical ACAS/ACST trials reported a 2% to 3% risk of stroke per year on medical therapy, a 2017 metaanalysis of more than 70% asymptomatic carotid stenosis reported that modern best medical therapy carries a pooled risk of 1.6% per year for ipsilateral stroke and 3.4% per year for transient ischemic attack. 20 However, the high variability of the stroke rate per year in these studies (0.34% as suggested by Marquardt et al 21 to 5.4% by the Aggressive Medical Treatment Evaluation for Asymptomatic Carotid Artery Stenosis study 22 ) made the results difficult to interpret. There are currently no data on the natural history of asymptomatic carotid stenosis in octogenarians.…”
Section: Journal Of Vascular Surgerymentioning
confidence: 87%
“… 11 15 On the other hand, publications with low stroke rates of ACS under BMT have been criticized for mixing patients with low-grade (50%–69%) and high-grade (≥70%) stenosis, having small patient numbers, not reporting adherence to BMT, neglecting transient ischemic attack (TIA)/high-risk plaque morphology and consecutive carotid revascularization (therefore preventing stroke), or discriminating insufficiently between ipsilateral and contralateral events. 16 Furthermore, two independent studies showed much higher annual rates of ipsilateral ischemic events in BMT (2.9% in a group of 1121 patients 17 and 2.4% in a group of 794 patients 18 ). However, in ACST-1, lipid-lowering therapy showed lower rates of long-term stroke in both groups, 19 indicating that stroke risk decreases with intensive medical therapy including statin medication 9 by plaque stabilization and consecutive reduction of microembolization.…”
Section: Introductionmentioning
confidence: 98%
“…The multivariate analysis identified female sex and age 80 years as independent predictors of uCEA condition. The higher risk of female sex on stroke severity was already established in the literature 15 and the older age is supposedly expression of the atherosclerotic burden of the patient and can justify these findings.…”
Section: Discussionmentioning
confidence: 76%